2017
DOI: 10.1111/bjep.12175
|View full text |Cite
|
Sign up to set email alerts
|

Self‐regulated learning from illustrated text: Eye movement modelling to support use and regulation of cognitive processes during learning from multimedia

Abstract: Our results indicate that EMME illustrating a comprehensive set of cognitive processes support multimedia learning for stronger university students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 28 publications
3
55
0
Order By: Relevance
“…Future studies should compliment self‐reported survey data with additional data sources such as think‐aloud‐protocols (e.g., Deekins, Green, & Lobczowski, ; Dinsmore & Zoellner, ) and eye‐tracking (e.g., Catrysse et al ., ; Scheiter, Schubert, & Schüler, ). Furthermore, the current research needs to be replicated in a wider variety of institutional and cultural contexts to check the conclusions from our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should compliment self‐reported survey data with additional data sources such as think‐aloud‐protocols (e.g., Deekins, Green, & Lobczowski, ; Dinsmore & Zoellner, ) and eye‐tracking (e.g., Catrysse et al ., ; Scheiter, Schubert, & Schüler, ). Furthermore, the current research needs to be replicated in a wider variety of institutional and cultural contexts to check the conclusions from our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Traces record information on which learners operatefor example, content highlighted or generated in notesand operations applied to informationfor example, metacognitively monitoring whether content is important or vague, or assembling content studied in a text with a personal example. Eye movement data like those analysed by Scheiter, Schubert, and Sch€ uler (2018) trace information to which learners attend. We have developed a software system called nStudy to gather trace data and return learning analytics as guides for learners' SRL (Winne et al, 2017a).…”
Section: Data About Levels Of Processing In Self-regulated Learningmentioning
confidence: 99%
“…Scheiter, Schubert, and Schüler, also focused on the role of knowledge in strategic processing. These researchers wanted to determine whether a substantial amount of domain knowledge would override university students’ use of a particular technique shown to be effective with elementary students’ reading of multimedia texts.…”
Section: Introductionmentioning
confidence: 99%